Yield Estimation and Factors Influencing Acceptance of Sweet potato Vines of Virus Free Varieties in Selected Agro-ecological Zones in Tanzania - Kibiki, Castory; Saidia, Paul; Shemahonge, Mohammed; Mihafu, Fabian (Discoveries in Agriculture and Food Sciences, 2024)
The effort of initiating the production and vine multiplication of sweetpotato using certified virus free vines focuses on promoting high yields towards enhancing food security and income generation among smallholder farmers. This study examines yield of sweetpotato tubers and vine multiplication per hectare using certified virus free vines in the Lake Victoria and Coastal Zones in Tanzania. Primary data were collected using questionnaire tool from 362 farmers who are sweetpotato tubers producers and 133 farmers who are producers of virus free vines. The sample was chosen from each selected agro-ecological zone by simple random sampling technique. The yield estimation was calculated using Microsoft Excel 2007 and the factors influencing uptake of variety was analyzed using Statistical Package for Social Science (SPSS ver. 20, IBM, USA). The study findings showed that, mean production of virus free sweetpotato tubers was relatively higher in the Lake Zone (1309.44kg) compare to Coastal Zone (1249.75kg). On the other hand, mean of vine multiplication was relatively higher in Coastal Zone (276.65kg) compared to Lake Zones (133.34kg). These results highlight that, the level of sweet potato yield depends on the amount of land used in production, as the farmers expand the cultivated area the amount of yield increases significantly. Gender, occupation, training and distance were some of the factors that influenced the acceptance of sweetpotato tubers and vine multiplication significantly at 10%. Therefore investing in the production of sweetpotato tubers and vine multiplication using quality variety which is free from virus is highly worth undertaking as the variety generates high quantity of yields per hectare.